2020
DOI: 10.1111/bjh.16304
|View full text |Cite
|
Sign up to set email alerts
|

Failure of rituximab is associated with a poor outcome in diffuse large B cell lymphoma‐type post‐transplant lymphoproliferative disorder

Abstract: Summary Post‐transplant lymphoproliferative disorder (PTLD) may arise after solid organ transplantation, and the most common subtype resembles diffuse large B cell lymphoma (DLBCL). In DLBCL‐type PTLD, the anti‐CD20 antibody rituximab (R) may be combined with chemotherapy (R‐CHOP) or use a strategy (R‐primary; similar to the PTLD‐1 clinical trial) consisting of induction with four weekly doses of R‐alone, without any chemotherapy or sequential R‐CHOP follow‐up. Here we report on a multicentre retrospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
4
12
1
Order By: Relevance
“…A recent ANZDATA study 12 showed an excess risk of death in kidney‐transplant recipients with PTLD, particularly in the first two years after diagnosis which fits with our landmark analysis. The number of deaths in our study (39/90, 43%, median follow‐up 5.9 years) is in keeping with a Canadian study restricted to DLBCL‐type PTLD treated with rituximab/R‐CHOP (82/168, 48%, median follow‐up 2.4 years) 13 . However, a larger proportion of patients died due to non‐lymphoma causes in our study (34% compared with 22% in the Canadian study).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A recent ANZDATA study 12 showed an excess risk of death in kidney‐transplant recipients with PTLD, particularly in the first two years after diagnosis which fits with our landmark analysis. The number of deaths in our study (39/90, 43%, median follow‐up 5.9 years) is in keeping with a Canadian study restricted to DLBCL‐type PTLD treated with rituximab/R‐CHOP (82/168, 48%, median follow‐up 2.4 years) 13 . However, a larger proportion of patients died due to non‐lymphoma causes in our study (34% compared with 22% in the Canadian study).…”
Section: Discussionsupporting
confidence: 87%
“…The number of deaths in our study (39/90, 43%, median follow-up 5.9 years) is in keeping with a Canadian study restricted to DLBCL-type PTLD treated with rituximab/R-CHOP (82/168, 48%, median follow-up 2.4 years). 13 However, a larger proportion of patients died due to non-lymphoma causes in our study (34% compared with 22% in the Canadian study). Burns et al reported a 12-month non-PTLD mortality of 7%, 9 compared to 25% and 17% in our R-Chemo and R-Mono groups respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…8 In two recent international, prospective, multicenter adult PTLD trials, more than half of the patients (53% and 62%) had EBV(−) PTLD. 15,23 In another large study, EBV(−) cases markedly increased over time from 10% (1990-1995) to 48% (2008-2013). 6 Whether the same trend has occurred in pediatric EBV(−) PTLD is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…End of treatment CR were 76.3% (29/38) and 81.8% (18/22), respectively. Jain et al 20 used a similar protocol on 109 patients (25% of PR patients treated by chemotherapy) and reported an R-induction CR rate of 43%.…”
Section: Discussionmentioning
confidence: 99%